PENGARUH VARIASI AIR SEBAGAI MEDIA PENDINGIN TERHADAP KEKERASAN HASIL PENGELASAN PADA BAJA ST- 37 - Putra, Bagoes Handika; Rahmadi, Hairian; Nurmayasari, Dewi; Helanianto, Helanianto (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2023)
This research will provide testing of low carbon steel, namely ST-37 Steel, through a welding process using cooling media with variations in water on the hardness of the steel resulting from welding. The important point in this research is to be able to determine the effect of the cooling medium on the hardness of the welded steel in order to obtain maximum hardness and obtain good weld hardness. Welding is carried out using the shielded metal ac welding (SMAW) welding method, so testing is required on test objects resulting from shielded metal ac welding (SMAW). The research method that the researcher took was an experimental research method, namely research to determine the consequences of the treatment given to the thing being researched by carrying out Rockwell Hardness (HR) testing. From the tests, differences were found in each specimen using 4 different water samples. The 4 water samples used were sea water, salt water, water with a pH of 6.1, and water with a pH of 7.4. Variations in cooling media influence the test results, namely at 10 specimen points tested from 4 cooling media samples, it was found that the specimen with the highest level of hardness was the specimen using a water sample with a pH of 6.1, namely with an average value of 49.3 (HR), and the specimen with the lowest level of hardness was the specimen with the salt water sample, with an average value of 46.95 (HR).